Use of Modern Information Technologies in Remote Servicing of Clients of Commercial Banks: International Experience and application Possibilities in Uzbekistan - Karimova Maxomadrizoevna, Aziza; Khursanova Erkinovna, Farida (THE INNOVATION ECONOMY, 2025)
the article explores the use of modern information technologies in the remote service of clients of commercial banks. It provides an overview of the international experience of the USA, Europe, and Russia in the field of banking digitalization, including the implementation of open banking, fintech solutions, and mobile platforms. Special attention is paid to Uzbekistan’s initiatives within the framework of the “Digital Uzbekistan – 2030” strategy, including the development of digital services, platforms such as Payme, Click, and the introduction of digital currency Security and risk management issues are analyzed, and recommendations are offered for applying international practices to the national banking system. It is proven that the development of remote banking services contributes to increasing financial inclusion, efficiency, and sustainable economic growth.